(untitled) (JURNAL ADMINISTRASI PUBLIK, 2015)
Abastrack: In accordance with the village development goals mandated in Law No. 6 of 2014, thus, the Utilization of Village Allocation Fund (ADD) is expected by the Government Bolaang North Mongondow can increase community participation in rural development in mutual cooperation. Rural development is directed to make optimum use of natural resources and human resources development by improving the quality of life, skills and initiative with guidance and assistance from the government. To find out how the Village Fund Allocation Utilization in promoting rural development in the village of Tanjung Sidupa District of North Mongondow Pinogaluman Bolaang. As for the benefits of this research are: (1) Purpose Theoretical results of this study are expected to be useful in the development of science related to the science of government. Especially in the analysis of the Village Fund Allocation Utilization (ADD). (2) Practical Uses results of this study are expected to contribute ideas on the implementation of the policy to the perpetrators of the policy and decision makers related to the development of regional development. In this regard the government to increase the capacity of the village, development and empowerment of rural communities need to gain greater attention, including through the pattern of allocation of funds pengelolahan village or the Village Fund Allocation (ADD). ADD is distributed to all villages in North Mongondow Bolaang fair and equitable manner and its use in accordance with the needs of the village. Based on the results of these studies in deduced that the utilization of the Village Fund Allocation (ADD) as a replacement for the use of development funds / District Village can increase community participation in village development in Tanjung Sidupa. Based on the conclusions of the research results it is suggested several things: (1) To intensify community participation in rural development. (2) Create a bulletin board in every village to announce the implementation report the use of ADD to be known by the whole community. Key Word :Village Fund Allocation (ADD), Rural Development